Optimization of hormonal dose during masculinization of tilapia (Oreochromis niloticus) fry - Ferdous, Z; Ali, MM (Journal of the Bangladesh Agricultural University, 2012)
The experiment was conducted to optimize the dose of 17?-methyl testosterone (MT) during masculinization of tilapia (Oreochromis niloticus) fry. Five treatments were designed with various doses of hormone to find out the most effective one. The treatments were designated as T1 (0 mg MT/kg), T2 (40 mg MT/kg), T3 (50 mg MT/kg), T4 (60 mg MT/kg) and T5 (70 mg MT/kg). MT was administered orally by using nursery feed and Ethanol (as hormone carrier solvents) diet to tilapia fry for 28 days in hapa. After completion of the trial period of 28 days nursing of the experimental fry was continued for further 2 months with commercial feed. At the end of experiment the sex ratio was determined by examining gonad after dissecting the fish. Growth performance was monitored by recording the morphometric characteristics i.e. weight gain (g), average daily weight gain (g). The analysis of growth data showed significant variation in weight, % weight gain, SGR (% /day) of fish among the different treatments. SGR increases with the increase of hormone dose. The present study demonstrated that all MT receiving treatments showed a significantly (p<0.01) higher male proportion (94.28%) than control (48.57%). The dose of 60 mg MT/kg of feed resulted in maximum male population (94.28%). The result indicated that the optimum dose of MT hormone was 60 mg /kg with a feeding period of 28 days after hatching. DOI: http://dx.doi.org/10.3329/jbau.v9i2.11052 J. Bangladesh Agril. Univ. 9(2): 359364, 2011